Oriented silicon steel large-tension coating material and preparation method thereof

By using raw materials such as acid silicon sol, mixed slurry, nanomagnesium oxide and nano zinc oxide, and heat treatment to form a patch-like zirconium tungstate coating, the existing tension coating is solved, and the effect of efficient refining magnetic domains, reducing iron losses and improving the cracking resistance of the coating is achieved.

CN119842253AActive Publication Date: 2025-04-18HUBEI WUZHOU NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510346137.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-18
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The existing tension coatings are prone to decomposition at high temperatures, resulting in reduced heat resistance and welding properties, insufficient crack resistance and short service life.

Method used

The coating is prepared by raw materials such as acid silicon sol, mixed slurry, nanomagnesium oxide and nano zinc oxide, and the coating is obtained by low-speed intermittent stirring and vacuum exhaust. Then heat treatment is carried out under an argon atmosphere to form a patch-like zirconium tungstate coating.

Benefits of technology

It improves the crack resistance of the coating, reduces the thermal expansion coefficient, enhances magnetic properties and reduces iron losses, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842253A_ABST
    Figure CN119842253A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal material surface coatings, and particularly discloses an oriented silicon steel large-tension coating material and a preparation method thereof. The paint of the high-tension coating is prepared by mixing the following raw materials in parts by mass: 70-80 parts of acidic silica sol, 15-20 parts of mixed slurry, 3-5 parts of nano magnesium oxide and 1.5-2 parts of nano zinc oxide; the preparation method comprises the following steps: taking acidic silica sol, adding nano magnesium oxide and zinc oxide, adjusting the stirring speed to 150-200rpm, stirring for 10-30 minutes, then adding mixed slurry, intermittently stirring for 25-30 minutes at a low speed, and then vacuumizing and exhausting at 0.01-0.03 Mpa to obtain the coating. The prepared oriented silicon steel large-tension coating material has excellent anti-cracking performance, and the thermal expansion coefficient under the test temperature condition of 200 DEG C is lower than 3.86 * 10 <-6 > / K; the iron loss is less than 0.92 W / kg, and the magnetic induction intensity is more than 1.71 T.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal material surface coating, and more specifically, to a high-tension coating material for oriented silicon steel and a preparation method thereof. Background Art

[0002] Oriented silicon steel is called a work of art in steel. It is a soft magnetic alloy with high magnetic flux density, mainly used to make the iron core of motors and transformers. Under the background of the dual carbon strategy, it is required to produce oriented silicon steel with better performance, especially oriented silicon steel with excellent magnetic properties. At present, in addition to adjusting the composition of oriented silicon steel to improve its magnetic properties, it is also possible to refine the magnetic domain and improve the magnetic properties by applying an insulating coating on the surface of oriented silicon steel and using the contact stress generated by the difference in thermal expansion coefficient between the coating and the silicon steel itself. Due to the difference in thermal expansion coefficient, a certain tension is formed between the insulating coating and the oriented silicon steel. Based on this feature, this coating is also called a tension coating. In addition to providing a certain tension, the tension coating also requires excellent insulation performance and adhesion performance on the magnesium silicate substrate. In order to meet these requirements and reduce production costs, phosphate, silica sol, chromic anhydride, water and other additives are usually mixed and heat treated to prepare the tension coating.

[0003] The Chinese patent application document with publication number CN104530782A discloses a phosphate coating solution and a preparation method thereof. The application provides a formula for an insulating coating solution, wherein aluminum dihydrogen phosphate, magnesium dihydrogen phosphate, chromic anhydride and silica sol are used as raw materials, and 0.5-1.5wt% of polyether modified silicone oil is added to improve leveling, and the coating is finally obtained after baking and high-temperature sintering. In the application scheme, oriented silicon steel needs to be stress-relieved annealed at high temperature before use to reduce iron loss, and the organic part in the coating is easily decomposed at high temperature, volatilizing harmful gases, resulting in a decrease in the heat resistance and weldability of the coating.

[0004] Nippon Steel Corporation of Japan has also formed a tension coating with SiO2 as the main component on the surface of oriented silicon steel strip through an oxidation reaction based on an insulating layer solution with iron oxide or iron hydroxide as the main component. The company has also developed an insulating treatment agent mainly composed of phosphate and colloidal silica. The insulating coating prepared by the agent has excellent adhesion and corrosion resistance, and the coating tension is also improved, thereby significantly improving the magnetic properties of oriented silicon steel.

[0005] After the above-mentioned coating is modified, although the tension properties of the obtained coating material are greatly improved, the process adopted in the scheme has high requirements on production equipment and technical control means. In addition, due to the poor anti-cracking performance of silica sol, one of the main components of the tension coating, the obtained tension coating often has a short service life. Therefore, there is still a need to find a tension coating that can effectively refine the magnetic domain, reduce iron loss and improve the anti-cracking properties of the coating. Summary of the invention

[0006] In order to further effectively refine the magnetic domains and reduce iron losses while enhancing the anti-cracking properties of the tension coating, the present application provides a high-tension coating material for oriented silicon steel and a preparation method thereof.

[0007] In the first aspect, the present application provides a method for preparing a high-tension coating material for oriented silicon steel, wherein the coating of the high-tension coating material is prepared by mixing the following raw materials in parts by weight: 70-80 parts of acidic silica sol, 15-20 parts of mixed slurry, 3-5 parts of nano magnesium oxide, and 1.5-2 parts of nano zinc oxide; the preparation steps include the following: Take acidic silica sol, add nano magnesium oxide and zinc oxide, mix, then add the mixed slurry, stir intermittently at a low speed for 25-30 minutes, and then evacuate and exhaust at 0.01-0.03Mpa to obtain the coating; The preparation steps of the mixed slurry include the following: [S01] Take zirconium nitrate, add water to dissolve it, and obtain liquid A; [S02] Take ammonium tungstate, add it into 5%-9% ammonia water, dissolve it, and obtain liquid B; [S03] Add 20%-25% by mass of dilute nitric acid and a crystal promoter to water, disperse, then adjust the temperature to 65-70°C, drip liquid A and liquid B into the system at the same time, adjust the magnetic stirring speed to 100-150rpm, treat for 3-4h, then filter out the flocculent precipitate, add a mixed dispersant to disperse, add water, adjust the magnetic stirring speed to 300-500rpm, disperse for 10-30min, and obtain a mixed slurry.

[0008] By adopting the above technical scheme, after the above steps, a mixed solution of acidic silica sol and zirconium tungstate precursor separated and dispersed can be obtained. During the subsequent coating calcination treatment, the molten zirconium tungstate diffuses at the boundary formed between it and the acidic silica sol component, and the isolation boundary is continuously eliminated. Finally, after cooling, a patchy distribution of zirconium tungstate coating parts is obtained.

[0009] Preferably, in steps [S01] and [S02], the mass volume ratio of zirconium nitrate, water, ammonium tungstate and aqueous ammonia is (7-7.2) g: (100-110) mL: (5.4-5.7) g: (65-75) mL.

[0010] By adopting the above technical solution, the ratio of the reactant raw materials is regulated to ensure that in the subsequent mixing process of A and B liquids, zirconium and tungsten elements react in a molar ratio close to 1:2, and by adjusting the reaction conditions, a zirconium tungstate (ZrW2O8) precursor is finally obtained.

[0011] Preferably, in step [S03], the crystal-promoting agent is nano-silicon dioxide with an average particle size of 100 nm.

[0012] By adopting the above technical solution, nano-silicon dioxide can be used as the nucleus for the growth of zirconium tungstate crystals in the subsequent heat treatment annealing stage, promoting the growth of zirconium tungstate grains to obtain a more regular crystal structure.

[0013] Preferably, in step [S03], the mixed dispersant is prepared by mixing sodium alkylbenzene sulfonate, hydroxyethyl cellulose and dichloromethane in a mass volume ratio of (0.3-0.5) g: (1.2-1.5) g: (50-55) mL.

[0014] By adopting the above technical solution, the mixed dispersant used can reduce the flocculation degree of the zirconium tungstate precursor, avoiding its excessive flocculation affecting the uniformity of subsequent blending with acidic silica sol. At the same time, the mixed dispersant is hydrophobic, and during blending, a layer of oil-water isolation film can be formed on the contact surface between the mixed slurry and the acidic silica sol, promoting the distribution behavior of the mixed slurry in the acidic silica sol system as small liquid groups. In the subsequent heat treatment baking stage, the dichloromethane in the mixed dispersant escapes, and the molten zirconium tungstate diffuses at the isolation film during calcination, and the isolation boundary is continuously eliminated, and finally a patchy distribution of the zirconium tungstate coating part is obtained.

[0015] Preferably, in step [S03], the volume ratio of the added water to the mixed solvent is (4-5): (1-1.5).

[0016] By adopting the above technical solution, the zirconium tungstate precursor is pre-dispersed using deionized water that is incompatible with the mixed dispersant. By utilizing the poor compatibility between the two solvents, the zirconium tungstate precursor droplets can be fully dispersed. The use of raw materials with this volume ratio has the best effect.

[0017] Preferably, the intermittent stirring is: stirring at a speed of 50-75 rpm for 2-3 min, then standing for 1-2 min, and repeating the above operation.

[0018] By adopting the above technical scheme, a metastable mixed slurry of acidic silica sol and mixed slurry can be obtained. The mixed slurry exists in the acidic silica sol as a dispersed state of droplets that are insoluble in other components. After subsequent heat treatment and cooling, patchy zirconium tungstate crystals are obtained.

[0019] In a second aspect, the present application provides a high-tension coating material for oriented silicon steel, which is obtained by the following steps: [I] Silicon steel pretreatment: take the silicon steel original sheet, grind it with sandpaper, immerse it in acid solution, wash it, isolate it from air and dry it, then apply magnesium oxide coating liquid, dry it under protective gas atmosphere, heat it at 1100-1175℃, and cool it at room temperature to obtain pretreated silicon steel; [II] Coating spraying and heat treatment: Take pretreated silicon steel, apply coating after preheating to obtain coated silicon steel, then heat treat it in an argon atmosphere and cool it down to obtain the coated silicon steel.

[0020] Preferably, in step [I], the magnesium oxide coating liquid is prepared by mixing nano magnesium oxide (30 nm) and deionized water in a mass volume ratio of 1 g: (5-7) mL; and the protective gas is prepared by mixing nitrogen with a volume fraction of 25% and hydrogen with a volume fraction of 75%.

[0021] By adopting the above technical solution, nano-magnesium oxide can be used as an isolation agent for high-temperature treatment of silicon steel to improve the ability of silicon steel to resist external erosion. Nano-magnesium oxide evenly dispersed on the surface of silicon steel can increase the hardness of the coating and reduce the wear of the coating. In the subsequent high-temperature sintering process in a protective gas atmosphere, nano-magnesium oxide reacts with silicon elements on the surface of silicon steel to form magnesium silicate, further improving the magnetic properties of silicon steel.

[0022] Preferably, in step [II], the heat treatment includes baking, calcining, and annealing, and the steps are as follows: Baking: Fix the coated silicon steel with a metal bracket, hang it in the oven, and bake it with hot air at 55-60℃ for 20-30min, then bake it at 220-240℃ for 30-40s; Calcination: Transfer the baked coated silicon steel to an atmosphere furnace and treat at 850-920℃ for 1-2min; Annealing: cooling at a rate of 5-7°C / min; In the annealing step, the temperature is gradually reduced to 45-50° C. in the furnace, and then the temperature is kept constant for 1-2 hours.

[0023] By adopting the above technical scheme, in the heat treatment baking operation, hot air baking can fully remove the interface separation solvent dichloromethane in the coating, eliminating the boundary between the zirconium tungstate precursor and the acidic silica sol in the previous coating; raising the temperature and baking again can fully remove the moisture in the coating, avoiding the influence of residual moisture on the coating during subsequent calcination. In the second stage of calcination, during the short-term high-heat treatment process, the solid part of the coating melts rapidly, and the components of the coating in the molten state diffuse with each other to form a diffuse crystal phase area. At this time, the molten coating has a high stress inside due to the influence of the instantaneous phase change. In the third stage of annealing operation, the slow cooling operation can eliminate the hardening area and residual stress, and finally obtain a uniform coating film. In the zirconium tungstate part, the nano-silicon dioxide dispersed therein serves as the crystal nucleus for the annealing crystallization of the molten zirconium tungstate, promoting the crystallization behavior of zirconium tungstate.

[0024] In summary, this application has the following beneficial effects: 1. This application uses a zirconium tungstate precursor obtained by the reaction of zirconium nitrate and ammonium tungstate as a component of the mixed slurry. The obtained zirconium tungstate precursor is a material with an excellent negative thermal expansion coefficient, which can be used to enhance the negative expansion coefficient of the coating and improve the tension properties of the coating. In the preparation of the mixed slurry, a solvent system in which water and dichloromethane are immiscible is constructed to enhance the subsequent dispersion effect of the zirconium tungstate precursor in the acidic silica sol; at the same time, during the heat treatment process, the solvent evaporates, and the coating melt diffuses to eliminate the dispersion boundary, and finally a coating material is obtained.

[0025] 2. In the present application, it is preferred to enhance the crack reinforcement effect of zirconium tungstate on the coating by heat treatment and dispersion treatment. After heat treatment and dispersion treatment, zirconium tungstate crystals are mixed in the coating material in the form of patches between the acidic silica sol-cured films. When the external environment changes, the difference in thermal expansion coefficient between silicon steel and the coating acts on the coating, exerting an outward-expanding tension force on the coating, promoting the thermal deformation behavior of the acidic silica sol-cured film. At this time, the dispersed zirconium tungstate shrinks due to heat, providing a tension buffer area for the silica sol-cured film and restraining the thermal deformation behavior of the surrounding acidic silica sol-cured film. Zirconium tungstate plays a role similar to a "patch" in the tension coating, inhibiting the cracking of the entire coating.

[0026] 3. The silicon steel high tension coating material prepared by the coating of the present application has excellent crack resistance, and the thermal expansion coefficient is less than 3.86×10 -6 / K; iron loss <0.92W / kg, magnetic induction intensity >1.71T. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the thermal expansion coefficient of the silicon steel high tension coating material of Examples 1-3 and Comparative Examples 1-2 of the present application.

[0028] Figure 2 Magnetic properties and iron loss of silicon steel high tension coating materials of Examples 1-3 of the present application and Comparative Examples 1-2. DETAILED DESCRIPTION

[0029] The raw material compositions of the silicon steel sheets used in Examples 1-3 and Comparative Examples 1-2 are shown in Table 1.

[0030] Table 1 Raw material composition of silicon steel sheet

[0031] Example 1 In this embodiment, the coating of the high tension coating is prepared by mixing the following raw materials by weight: 70g of acidic silica sol, 15g of mixed slurry, 3g of nano magnesium oxide, and 1.5g of nano zinc oxide; the specific preparation steps are as follows: Take acidic silica sol, add nano magnesium oxide (30nm) and nano zinc oxide (50nm), adjust the magnetic stirring speed to 150rpm, stir for 10min, then add the mixed slurry, stir for 2min at a magnetic stirring speed of 50rpm, then let stand for 1min and intermittently stir for 25min, finally evacuate at 0.01Mpa, let stand for 0.5h to obtain the coating material.

[0032] In this embodiment, the steps for preparing the mixed slurry are as follows: [S01] Take 7 g of zirconium nitrate and dissolve it in 100 mL of deionized water to obtain solution A; [S02] Take 5.4 g of ammonium tungstate and dissolve it in 65 mL of 5% ammonia water to obtain liquid B; [S03] Take 150mL of deionized water, add 30mL of 20% dilute nitric acid and 0.2g of nano-silicon dioxide (100nm), adjust the magnetic stirring speed to 200rpm, disperse for 1min, then increase the system temperature to 65℃, control the magnetic stirring speed to 100rpm, and drop liquid A and liquid B into the system at a drop rate of 5mL / min, respectively, and treat for 3h under constant temperature conditions. Then filter and take the flocculent precipitate, add 45mL of mixed dispersant and disperse for 20min, then add 10mL of deionized water, increase the magnetic stirring speed to 300rpm, and continue stirring for 10min to obtain a mixed slurry.

[0033] In this embodiment, the steps for preparing the oriented silicon steel high tension coating material are as follows: [I] Silicon steel pretreatment: Take a 250mm×70mm×2mm silicon steel sheet, polish the surface with 800-grit sandpaper, immerse it in a 5% dilute sulfuric acid solution for 0.5h, wash it twice with anhydrous ethanol, isolate it from the air and dry it, then use a paint roller to apply 1.62g / m 2A layer of magnesium oxide coating is applied on the silicon steel with a coating amount of , and after coating, it is placed in an oven at 70°C for 1 hour. Then the silicon steel is transferred to an atmosphere furnace, and the temperature in the furnace is increased to 1100°C at a heating rate of 50°C / h under a protective gas atmosphere. After keeping the temperature constant for 1 hour, it is transferred to room temperature and naturally cooled to obtain the pretreated silicon steel.

[0034] [II] Coating spraying and heat treatment: The pre-treated silicon steel was placed in an oven and preheated at 30°C, and then a coating roller was used to spray the pre-treated silicon steel at 3.24 g / m 2 The coating is applied on the pretreated silicon steel with a coating amount of , to obtain coated silicon steel. Then the coated silicon steel is fixed with a metal bracket, suspended in an oven, and baked at 55℃ hot air slow flow for 20min under argon atmosphere, and then baked at 220℃ for 30s. After baking, the coated silicon steel is transferred to an atmosphere furnace, maintained at argon atmosphere, and treated at 850℃ for 1min. Finally, the furnace temperature is reduced to 45℃ at a cooling rate of 5℃ / min, and the temperature is kept constant for 1h to complete the heat treatment. After cooling, the oriented silicon steel high tension coating material is obtained.

[0035] Among them, acidic silica sol (model SW-20, SiO2%wt: 30%) was provided by Dongying Yiming New Materials Co., Ltd. Zirconium nitrate (purity 99.5%) was provided by Jining Huicheng New Materials Co., Ltd. Ammonium tungstate (purity 99.9%) was provided by Shanghai Linghao Metal Materials Co., Ltd. The mixed dispersant was prepared by mixing sodium alkylbenzene sulfonate, hydroxyethyl cellulose, and dichloromethane in a mass volume ratio of 0.3g:1.2g:50mL. The magnesium oxide coating liquid was prepared by mixing nano magnesium oxide (30nm) and deionized water in a mass volume ratio of 1g:5mL. The protective gas was a mixture of 25% by volume nitrogen and 75% by volume hydrogen.

[0036] Example 2 In this embodiment, the coating of the high tension coating is prepared by mixing the following raw materials by weight: 75g of acidic silica sol, 16g of mixed slurry, 4g of nano magnesium oxide, and 1.75g ​​of nano zinc oxide; the specific preparation steps are as follows: Take acidic silica sol, add nano magnesium oxide (30nm) and nano zinc oxide (50nm), adjust the magnetic stirring speed to 150rpm, stir for 20min, then add the mixed slurry, stir for 2min at a magnetic stirring speed of 60rpm, then let stand for 1min and intermittently stir for 30min, finally evacuate at 0.02Mpa, let stand for 0.5h to exhaust and obtain the coating material.

[0037] In this embodiment, the steps for preparing the mixed slurry are as follows: [S01] Take 7.1 g of zirconium nitrate and dissolve it in 105 mL of deionized water to obtain liquid A; [S02] Take 5.5 g of ammonium tungstate and dissolve it in 70 mL of 8% ammonia water to obtain liquid B; [S03] Take 150mL of deionized water, add 30mL of 25% dilute nitric acid and 0.3g of nano-silicon dioxide (100nm), adjust the magnetic stirring speed to 225rpm, disperse for 1min, then increase the system temperature to 70℃, control the magnetic stirring speed to 150rpm, and drop liquid A and liquid B into the system at a drop rate of 7mL / min, respectively, and treat for 4h under constant temperature conditions. Then filter and take the flocculent precipitate, add 50mL of mixed dispersant and disperse for 30min, then add 15mL of deionized water, increase the magnetic stirring speed to 500rpm, and continue stirring for 15min to obtain a mixed slurry.

[0038] In this embodiment, the steps for preparing the oriented silicon steel high tension coating material are as follows: [I] Silicon steel pretreatment: Take a 250mm×70mm×2mm silicon steel sheet, polish the surface with 800-grit sandpaper, immerse it in a 7.5% dilute sulfuric acid solution for 1 hour, wash it with anhydrous ethanol three times, and then isolate it from the air and dry it. Then use a paint roller to apply 1.67g / m 2 A layer of magnesium oxide coating is applied on the silicon steel with a coating amount of , and after coating, it is placed in an oven at 75°C for 2h, and then the silicon steel is transferred to an atmosphere furnace, and the temperature in the furnace is increased to 1150°C at a heating rate of 65°C / h under a protective gas atmosphere, and after keeping the temperature constant for 2h, it is transferred to room temperature and naturally cooled to obtain the pretreated silicon steel.

[0039] [II] Coating spraying and heat treatment: The pre-treated silicon steel was placed in an oven and preheated at 35°C, and then a coating roller was used to spray the pre-treated silicon steel at 3.35 g / m 2 The coating is applied on the pretreated silicon steel with a coating amount of coating to obtain coated silicon steel. Then the coated silicon steel is fixed with a metal bracket, suspended in an oven, and baked at 60℃ hot air slow flow for 30min under argon atmosphere, and then baked at 230℃ for 35s. After baking, the coated silicon steel is transferred to an atmosphere furnace, maintained at argon atmosphere, and treated at 900℃ for 1.5min. Finally, the furnace temperature is reduced to 50℃ at a cooling rate of 6℃ / min, and the temperature is kept constant for 1.5h to complete the heat treatment. After cooling, the oriented silicon steel high-tension coating material is obtained.

[0040] Among them, acidic silica sol (model SW-20, SiO2%wt: 30%) was provided by Dongying Yiming New Materials Co., Ltd. Zirconium nitrate (purity 99.5%) was provided by Jining Huicheng New Materials Co., Ltd. Ammonium tungstate (purity 99.9%) was provided by Shanghai Linghao Metal Materials Co., Ltd. The mixed dispersant was prepared by mixing sodium alkylbenzene sulfonate, hydroxyethyl cellulose, and dichloromethane in a mass volume ratio of 0.4g:1.5g:50mL. The magnesium oxide coating liquid was prepared by mixing nano magnesium oxide (30nm) and deionized water in a mass volume ratio of 1g:6mL. The protective gas was a mixture of 25% by volume nitrogen and 75% by volume hydrogen.

[0041] Example 3 In this embodiment, the coating of the high tension coating is prepared by mixing the following raw materials by weight: 80g of acidic silica sol, 20g of mixed slurry, 5g of nano magnesium oxide, and 2g of nano zinc oxide; the specific preparation steps are as follows: Take acidic silica sol, add nano magnesium oxide (30nm) and nano zinc oxide (50nm), adjust the magnetic stirring speed to 200rpm, stir for 30min, then add the mixed slurry, stir for 3min at a magnetic stirring speed of 75rpm, then let stand for 2min and intermittently stir for 30min, finally evacuate at 0.03Mpa, let stand for 1h to exhaust, and then obtain the coating material.

[0042] In this embodiment, the steps for preparing the mixed slurry are as follows: [S01] Take 7.2 g of zirconium nitrate and dissolve it in 110 mL of deionized water to obtain liquid A; [S02] Take 5.7 g of ammonium tungstate and dissolve it in 75 mL of 9% ammonia water to obtain liquid B; [S03] Take 175mL of deionized water, add 35mL of 25% dilute nitric acid and 0.3g of nano-silicon dioxide (100nm), adjust the magnetic stirring speed to 250rpm, disperse for 2min, then increase the system temperature to 70℃, control the magnetic stirring speed to 150rpm, and drop liquid A and liquid B into the system at a drop rate of 8mL / min, respectively, and treat for 4h under constant temperature conditions. Then filter and take the flocculent precipitate, add 50mL of mixed dispersant and disperse for 30min, then add 15mL of deionized water, increase the magnetic stirring speed to 500rpm, and continue stirring for 30min to obtain a mixed slurry.

[0043] In this embodiment, the steps for preparing the oriented silicon steel high tension coating material are as follows: [I] Silicon steel pretreatment: Take a 250mm×70mm×2mm silicon steel sheet, polish the surface with 800-grit sandpaper, immerse it in a 7.5% dilute sulfuric acid solution for 1 hour, wash it with anhydrous ethanol three times, and then isolate it from the air and dry it. Then use a paint roller to apply 1.72g / m 2 A layer of magnesium oxide coating is applied on the silicon steel with a coating amount of , and after coating, it is placed in an oven at 75 ℃ for 2 hours, and then the silicon steel is transferred to an atmosphere furnace. The temperature in the furnace is increased to 1175 ℃ at a heating rate of 75 ℃ / h under a protective gas atmosphere, and after maintaining the temperature for 2 hours, it is transferred to room temperature and naturally cooled to obtain the pretreated silicon steel.

[0044] [II] Coating spraying and heat treatment: The pre-treated silicon steel was placed in an oven and preheated at 35°C, and then a coating roller was used to spray the pre-treated silicon steel at 3.62 g / m 2 The coating is applied on the pretreated silicon steel with a coating amount of , to obtain coated silicon steel. Then, the coated silicon steel is fixed with a metal bracket, suspended in an oven, and baked at 60℃ hot air slow flow for 30min under argon atmosphere, and then baked at 240℃ for 40s. After baking, the coated silicon steel is transferred to an atmosphere furnace, maintained at argon atmosphere, and treated at 920℃ for 2min. Finally, the furnace temperature is reduced to 50℃ at a cooling rate of 7℃ / min, and the temperature is kept constant for 2h to complete the heat treatment. After cooling, the oriented silicon steel high tension coating material is obtained.

[0045] Among them, acidic silica sol (model SW-20, SiO2%wt: 30%) was provided by Dongying Yiming New Materials Co., Ltd. Zirconium nitrate (purity 99.5%) was provided by Jining Huicheng New Materials Co., Ltd. Ammonium tungstate (purity 99.9%) was provided by Shanghai Linghao Metal Materials Co., Ltd. The mixed dispersant was prepared by mixing sodium alkylbenzene sulfonate, hydroxyethyl cellulose, and dichloromethane in a mass volume ratio of 0.5g:1.5g:55mL. The magnesium oxide coating liquid was prepared by mixing nano magnesium oxide (30nm) and deionized water in a mass volume ratio of 1g:7mL. The protective gas was a mixture of nitrogen with a volume fraction of 25% and hydrogen with a volume fraction of 75%.

[0046] Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that an equal amount of combined liquid is used to replace the mixed slurry.

[0047] The combined liquid is obtained by uniformly mixing aluminum dihydrogen phosphate, deionized water, and boric acid in a mass volume ratio of 15 g:25 mL:1.5 g.

[0048] The remaining steps are the same as those in Example 1.

[0049] Comparative Example 2 The difference between this comparative example and Example 1 is that the coating of the high tension coating is prepared by mixing the following raw materials by weight: 90 g of acidic silica sol, 5 g of mixed slurry, 3 g of nano magnesium oxide, and 1.5 g of nano zinc oxide.

[0050] The remaining steps are the same as those in Example 1.

[0051] Performance testing Thermal Expansion Coefficient Test Referring to the national standard GB / T44536-2024 "Test method for thermal expansion coefficient and residual stress of CVD ceramic coating", the thermal expansion coefficient of the coatings of Examples 1-3 and Comparative Examples 1-2 was tested and analyzed at 200°C, 400°C, and 600°C, respectively. The test results are as follows: Figure 1 shown.

[0052] Magnetic properties and iron loss test Referring to the national standard GB / T3655-2022 "Method for measuring the magnetic properties of electrical steel strips (sheets) using Epstein square rings", the magnetic field strength was adjusted to 800A / m, and the magnetic properties of the silicon steel high tension coating materials of each group of Examples 1-3 and Comparative Examples 1-2 were tested. The magnetic induction intensity was controlled to 1.6T and the frequency was 45Hz. The iron loss of each group was tested. The test results are as follows: Figure 2 shown.

[0053] Coating property testing 1.1 Surface quality The coating is evaluated based on its leveling properties, coating appearance, and whether the surface is sticky after coating and drying.

[0054] 1.2 Corrosion resistance The corrosion resistance test is carried out in a circulating corrosion box. Corrosion conditions: spray with 5% saline solution for 5 hours at 35°C, and observe the surface of the sample after taking it out. The corrosion resistance evaluation standard is: rust area <5% is excellent; rust area 5%-29% is good; rust area 30%-59% is fair; rust area >60% is poor.

[0055] 1.3 Temperature change cracking test The silicon steel high tension coating materials of Examples 1-3 and Comparative Examples 1-2 were placed in a 450°C atmosphere furnace for 2 hours, then taken out and inserted into water for 10-15 seconds. After being taken out, they were allowed to stand at room temperature for 0.5 hours, the number of cracks and the maximum crack length on the measured surface were observed, and the cracks were rated according to the length. The rating standards are shown in Table 2.

[0056] Table 2 Rating standards for temperature change cracking test of silicon steel high tension coating materials in Examples 1-3 and Comparative Examples 1-2

[0057] The coating property test results are shown in Table 3.

[0058] Table 3 Test results of coating properties of Examples 1-3 and Comparative Examples 1-2

[0059] Analyze Examples 1-3 and Comparative Examples 1-2 and combine Figure 1 It can be seen that with the increase of the test temperature, the thermal expansion coefficient of the coating materials of the embodiment and the comparative scheme gradually increases. Among the five schemes, the starting point and the change rate of the thermal expansion coefficient of comparative example 2 are at a relatively high level in the test scheme. This is because, in the comparative example 2 scheme, only a mixed slurry with a percentage of 5.6% of silica sol is added, and the mixed slurry only plays a weak role in reducing the thermal expansion coefficient in the coating. Therefore, the comparative example 2 scheme performs the worst among the five test schemes.

[0060] Analyze Examples 1-3 and Comparative Examples 1-2 and combine Figure 2 It can be seen that the iron loss and magnetic properties of the silicon steel coating material are approximately inversely correlated, which is consistent with the objective properties of the material. Among the five test schemes, the coating materials of Example 2 and Example 3 have relatively excellent properties, showing relatively excellent effects in reducing iron loss and optimizing magnetic domains.

[0061] By analyzing Examples 1-3 and Comparative Examples 1-2 and combining with Table 3, it can be seen that in terms of comprehensive properties of the coating, the embodiment schemes show better test results than the comparative examples, while in Comparative Example 2, due to the selection of a scheme with a low ratio of acidic silica sol to mixed slurry, the coating properties are slightly reduced. Among the five schemes, the test effect of Comparative Example 1 is the worst.

[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a high-tension coating material of oriented silicon steel, characterized in that: The coating of the high tension coating material is prepared by mixing the following raw materials in parts by weight: 70-80 parts of acidic silica sol, 15-20 parts of mixed slurry, 3-5 parts of nano magnesium oxide, and 1.5-2 parts of nano zinc oxide; the preparation steps include the following: Take acidic silica sol, add nano magnesium oxide and zinc oxide, mix, then add the mixed slurry, stir intermittently at a low speed for 25-30 minutes, and then evacuate and exhaust at 0.01-0.03Mpa to obtain the coating; The preparation steps of the mixed slurry include the following: [S01] Take zirconium nitrate, add water to dissolve it, and obtain liquid A; [S02] Take ammonium tungstate, add it into 5%-9% ammonia water, dissolve it, and obtain liquid B; [S03] Add 20%-25% by mass of dilute nitric acid and a crystal promoter to water, disperse, then adjust the temperature to 65-70°C, drip liquid A and liquid B into the system at the same time, adjust the magnetic stirring speed to 100-150rpm, treat for 3-4h, then filter out the flocculent precipitate, add a mixed dispersant to disperse, add water, adjust the magnetic stirring speed to 300-500rpm, disperse for 10-30min, and obtain a mixed slurry.

2. The method for preparing a oriented silicon steel high tension coating material according to claim 1, characterized in that: The stirring speed during the mixing is 150-200 rpm and lasts for 10-30 minutes.

3. The method for preparing a oriented silicon steel high tension coating material according to claim 2, characterized in that: In the steps [S01] and [S02], the mass volume ratio of zirconium nitrate, water, ammonium tungstate and aqueous ammonia is (7-7.2) g: (100-110) mL: (5.4-5.7) g: (65-75) mL.

4. The method for preparing a oriented silicon steel high tension coating material according to claim 2, characterized in that: In the step [S03], the crystal-promoting agent is nano-silicon dioxide with an average particle size of 100 nm.

5. The method for preparing a oriented silicon steel high tension coating material according to claim 2, characterized in that: In the step [S03], the mixed dispersant is prepared by mixing sodium alkylbenzene sulfonate, hydroxyethyl cellulose, and dichloromethane in a mass volume ratio of (0.3-0.5) g: (1.2-1.5) g: (50-55) mL.

6. The method for preparing a oriented silicon steel high tension coating material according to claim 1, characterized in that: The intermittent stirring is: stirring at a speed of 50-75 rpm for 2-3 minutes, then standing for 1-2 minutes, and repeating the above operation.

7. A oriented silicon steel high tension coating material obtained by the preparation method according to any one of claims 1 to 6, which is obtained by the following steps: [I] Silicon steel pretreatment: take the silicon steel original sheet, grind it with sandpaper, immerse it in acid solution, wash it, isolate it from air and dry it, then apply magnesium oxide coating liquid, dry it under protective gas atmosphere, heat it at 1100-1175℃, and cool it at room temperature to obtain pretreated silicon steel; [II] Coating spraying and heat treatment: Take pretreated silicon steel, apply coating after preheating to obtain coated silicon steel, then heat treat it in an argon atmosphere and cool it down to obtain the coated silicon steel.

8. The oriented silicon steel high tension coating material according to claim 7, characterized in that: In the step [I], the magnesium oxide coating liquid is prepared by mixing nano magnesium oxide (30 nm) and deionized water in a mass volume ratio of 1 g: (5-7) mL; the protective gas is prepared by mixing nitrogen with a volume fraction of 25% and hydrogen with a volume fraction of 75%.

9. The oriented silicon steel high tension coating material according to claim 7, characterized in that: In step [II], the heat treatment includes baking, calcining, and annealing, and the steps are as follows: Baking: Fix the coated silicon steel with a metal bracket, hang it in the oven, and bake it with hot air at 55-60℃ for 20-30min, then bake it at 220-240℃ for 30-40s; Calcination: Transfer the baked coated silicon steel to an atmosphere furnace and treat at 850-920℃ for 1-2min; Annealing: Cool down at a rate of 5-7°C / min.

10. The oriented silicon steel high tension coating material according to claim 9, characterized in that: In the annealing step, the temperature is gradually reduced to 45-50° C. in the furnace, and then the temperature is kept constant for 1-2 hours.

Citation Information

Patent Citations

  • Phosphate coating solution and preparation method thereof

    CN104530782A

  • Insulating coating liquid for improving cracks of surface coating of oriented silicon steel, preparation method for insulating coating liquid, and oriented silicon steel plate

    CN112239863A

  • Grain orientated magnetic steel sheet with insulating film and method of producing the same

    JP2019151921A

  • Functional coating structure using negative thermal expansion material, manufacture method thereof, and micro gearing device using the same

    KR1020150144615A

  • Preparation method of crystalline zirconium tungstate having negative thermal expansion

    KR1020180038845A